A balanced tri‐band bandpass filter with high selectivity and controllable bandwidths. Issue 12 (30th September 2019) - Yang, Yong; Wang, Zanxian; Xu, Le; Liu, Yaxin
Abstract: In this article, a balanced tri‐band bandpass filter (BPF) with high selectivity and controllable bandwidths is proposed. Two differential‐mode (DM) passbands are formed by applying stepped impedance resonators into the design. Uniform impedance resonators are introduced to realize the third DM passband. Moreover, frequencies and bandwidths of DM passbands can be independently controlled by the lengths of resonators and the gaps between them. In addition, good DM transmission can be realized while high common‐mode suppression is achieved intrinsically without affecting the DM parts, thereby simplifying the design procedure significantly. In order to validate the practicability, a balanced tri‐band BPF operating at 2.45 GHz, 3.5 GHz, and 4.45 GHz is fabricated and designed. A good agreement between the simulated and measured results is observed.